On the fundamental solution of the Cauchy problem for Kolmogorov systems of the second order - Burtnyak, I. V.; Malyts’ka, H. P. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We study the structure of the fundamental solution of the Cauchy problem for a class of ultraparabolic equations with finitely many groups of variables degenerating parabolicity.